Being hit twice: The psychological consequences of the economic crisis and an earthquake. (June 2016) - Starace, Fabrizio; Mungai, Francesco; Sarti, Elena; Addabbo, Tindara
Background: The Great Recession has caused worldwide tangible costs in terms of cuts in employment and income, which have been widely recognised also as major social determinants of mental health. Italy has not been spared from the financial crisis with severe societal and mental health consequences. In addition, a strong earthquake hit the province of Modena, Italy, in 2012, that is, amid the crisis. Aims: In this study, we explored and investigated the possible additional impact of concurrent events such as economic crisis and a natural disaster. Methods: Our analysis elaborated data from two local surveys, ICESmo2 (2006) and ICESmo3 (2012), and a national survey carried out in 2013 by the Italian National Institute of Statistics (Istituto Nazionale di Statistica (ISTAT)). A regression model was adopted to distinguish the effect of the crisis and the earthquake. Results: Our analysis confirmed the negative effect of the economic crisis on psychological wellbeing, but within the province of Modena such an effect resulted as even stronger compared with the rest of Italy, particularly within those areas struck by the earthquake. Conclusion: Being hit by a combination of two major negative events might have a significantly increased negative effect on psychological health. The higher repercussion observed is not only attributable to the occurrence of a natural disaster but can be reasonably related to the additional effect of unemployment on psychological dimensions.